The role of haematopoietic stem cell transplantation for sickle cell disease in the era of targeted disease-modifying therapies and gene editing. Issue 12 (December 2020) - de la Fuente, Josu; Gluckman, Eliane; Makani, Julie; Telfer, Paul; Faulkner, Lawrence; Corbacioglu, Selim; ,; Amrolia, Persis; Ansari, Marc; Balduzzi, Adriana; Dalassier, Arnaud; Dalle, Jean-Hugues; et al.
Summary: Sickle cell disease is one of the most common, life-threatening, non-communicable diseases in the world and a major public health problem. Following the implementation of simple preventive and therapeutic modalities, infant mortality has almost been abolished in high-income countries, but only a small amount of progress has been made in improving survival in adulthood. Progressive end-organ damage, partly related to a systemic vasculopathy, is increasingly recognised. With the availability of a variety of novel disease-modifying drugs, gene addition and gene editing strategies, matched sibling donor haematopoietic stem cell transplantation (HSCT) in children (offering an overall survival rate of 95% and an event-free survival rate of 92%), and encouraging outcomes after alternative donor HSCT, the new challenge is to risk stratify patients, revise transplantation indications, and define the best therapeutic approach for each patient. The ultimate challenge will be to enable these advances in low-income and middle-income countries, where disease prevalence is highest and where innovative strategies are most needed.